“El aprendizaje significativo y las herramientas tecnológicas” - Toaquiza Vega, Joel Neptalí (2022)
The present research project was carried out with the objective of designing resources digital for the strengthening of meaningful learning for all areas of the Basic General Education curriculum, at the "Rotary Club" School, emphasizing in the sixth grade; Considering that technological tools are very important when developing the class, helping to make it more dynamic and to achieve a significant learning, since it is very essential to achieve meaningful learning.effective on the student. The basic education school is located in the Latacunga Canton of the Cotopaxi Province, Eloy Alfaro parish, the approaches the scientific approach - naturalistic and the scientific - positivist with the quantitative and qualitative methodology with which method applied was the inductive and the deductive, through survey techniques and interview therefore the instruments used were the questionnaire and the interview guide that allowed to collect the information, interpret, explain, and explore relevant aspects of the tools digital technologies to promote meaningful learning. The purpose of this project is to promote meaningful learning through the use of of technological tools to strengthen the training process. Finally, this research project contributes to the processes of innovation in the classroom through the incorporation of technology as a useful tool for trying to better development the teaching and learning process.